The Urgency of Cyber Education in Islamic Education for Indonesia's Golden Generation 2045: A Conceptual Analysis - Sumarni, Sri (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
In the context of Indonesia's ambitious goal to cultivate a Golden Generation by 2045, this article examines the urgent need to integrate cyber education within Islamic educational systems. Through a conceptual analysis grounded in descriptive qualitative methods, the study synthesizes insights from 42 recent scholarly works to propose a strategic framework for embedding digital technologies in Islamic pedagogy. The analysis reveals that cyber education, characterized by its interactivity, flexibility, and global reach, holds transformative potential for Islamic schools. However, its adoption is constrained by significant obstacles, including inadequate technological infrastructure, educators' insufficient digital skills, and a lack of coherent policy frameworks. A SWOT analysis further elucidates the strengths, weaknesses, opportunities, and threats associated with cyber education in this context. To overcome these challenges, the study advocates for a comprehensive strategy that includes digital literacy programs, collaborative efforts among stakeholders, and curriculum innovations that harmonize technological advancements with Islamic values. While the research is conceptual and requires empirical substantiation, it offers a valuable foundation for policymakers and educators. The article recommends conducting empirical studies to validate the conceptual model across various educational settings and to foster innovative practices that ensure Islamic education remains relevant and competitive in the digital era.